Implementation of a Finite State Machine for Character Animation Transitions in Unity-Based 3D Games - Muhammad Fairul Filza; Ahmad Zaid Rahman; Nadea Cipta Laksmita; Haryoko; Jedidta Adoni Saputra (Gayaku Publisher, 2025)
A responsive character animation system with smooth transitions is a crucial factor in creating a high-quality and immersive gameplay experience. A common issue that frequently arises is animation that appears rigid or unnatural when a character switches from one action to another. This study aims to implement a Finite State Machine (FSM) to manage player character animation transitions in the game Legacy of the Sunstone. The method employed is a Hierarchical Finite State Machine (HFSM) with Moore Machine characteristics, in which the output in the form of animation is determined by the currently active state at a given time. The implementation was carried out using the Unity Engine and applied the State Pattern to establish a structured, modular, and maintainable code architecture. The CrossFadeInFixedTime technique was utilized to achieve smooth animation blending between states with configurable transition durations. The developed FSM system consists of two main categories: Locomotion states, including Idle, Movement, Jump, Falling, and Crouch, and Combat states, including Aim, Melee, and Takedown. System testing can be conducted using Black Box Testing through an iterative approach across 13 test scenarios that cover all functional requirements of the system.